1985
DOI: 10.1021/la00061a004
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metal promoters and catalysts: a single-crystal investigation of ethylene epoxidation on cesium-doped silver(111)

Abstract: Cs adsorbs on Ag(lll) to form layers of relatively low atomic density; unlike the other alkalis, it does not significantly penetrate the Ag lattice. Multilayer growth proceeds by the Frank-van der Merwe mechanism, but oxygen chemisorption followed by heating drastically perturbs the structure of the alkali film; bare Ag sites are created, and there is evidence for the formation of higher oxides of Cs. The desorption properties of the system suggest that oxygen can induce the formation of a "surface alloy". The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 2 publications
2
34
1
Order By: Relevance
“…In this mechanism, Cs is thought to be responsible for blocking adsorption of oxygen onto these inherently less selective sites. This contradicts earlier work by Lambert and coworkers [25][26][27] who argued that Cs promotion was mainly electronic in nature. In their interpretation, Cs affected the secondary chemistry by decreasing the rate of EO isomerization to acetaldehyde [reaction (r 3 )], which at typical reaction conditions combusts immediately in the presence of Ag.…”
Section: Introductioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In this mechanism, Cs is thought to be responsible for blocking adsorption of oxygen onto these inherently less selective sites. This contradicts earlier work by Lambert and coworkers [25][26][27] who argued that Cs promotion was mainly electronic in nature. In their interpretation, Cs affected the secondary chemistry by decreasing the rate of EO isomerization to acetaldehyde [reaction (r 3 )], which at typical reaction conditions combusts immediately in the presence of Ag.…”
Section: Introductioncontrasting
confidence: 88%
“…The O 2 adsorption stoichiometry was assumed to be ½ O 2 /Ag = 1 (as used by Vannice) to give a Ag dispersion of 0.95%, corresponding to an average Ag diameter of 0.12 lm. Titration with O 2 for samples containing Cs, Re, and Mo was not performed because Cs [25], Re [47], and Mo [48] might interact with O 2 , which would skew the results and make accurate calculations of the average Ag particle sizes unreliable.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier surface science studies [12][13][14][15][16][17][18][19][20] of Ag-catalyzed ethylene epoxidation primarily addressed the roles of oxygen and promoters. By the late 1980s, a reasonable consensus emerged that addition of atomic, rather than molecular, oxygen to the double bond of ethylene led to epoxide formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, it has also been suggested that cesium plays a role in binding and dispersing the silver crystals on the catalyst support, as well as increasing the adsorption probability of oxygen on silver [15][16][17][18][19]. According to Minahan and co-workers [20], Cs acts as a binder between the Al 2 O 3 surface and the Ag crystallites to give a more uniform and higher coverage of the Ag component.…”
Section: Introductionmentioning
confidence: 99%